Induction of xylanolytic activity in Aureobasidium pullulans using xerographic paper - Marques, Susana (2009)
The possibility of using cheaper culture media for endo-1,4-b-xylanase production by the color variant-derivative strain of Aureobasidium pullulans Y-2311-1, one of the known best producers of this activity, was investigated. Of all the studied alternative substrates, xerographic paper showed to be the best inducer of xylanolytic activity of this strain, using different carbon sources. The highest extracellular xylanase activity obtained was 15 U/mL when using lactose as the carbon source in the presence of xerographic paper.